2017
DOI: 10.1002/slct.201601550
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amidoamine) Dendrimer Functionalized Carbon Nanotube for Efficient Sorption of Trivalent f‐Elements: A Comparison Between 1st And 2nd Generation

Abstract: Poly(amidoamine) dendrimer functionalized carbon nano tubes were synthesized, characterized and used for the sorption of americium from aqueous acidic waste solution. The sorption of Am3+ has been found to take place through pseudo second order kinetics with the rate constants of 8.61E‐05 and 5.38E‐05 mg g−1 min−1for 1st and 2nd generation, respectively, followingLangmuir isotherm. The MWCNT‐PAMAMG1 and MWCNT‐PAMAMG2 have high radiolytic stability. The stripping study revealed that EDTA can be effectively used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This interaction is suggested to be on the line of the solvent extraction equillibria where metal–ligand complexation is the key to metal ion extraction . Analogous sorption isotherm studies are reported in the literature where functionalized carbon naotubes have been used. , …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This interaction is suggested to be on the line of the solvent extraction equillibria where metal–ligand complexation is the key to metal ion extraction . Analogous sorption isotherm studies are reported in the literature where functionalized carbon naotubes have been used. , …”
Section: Resultsmentioning
confidence: 94%
“…26 Analogous sorption isotherm studies are reported in the literature where functionalized carbon naotubes have been used. 45,46 Column Studies. Column experiments were performed with a feed solution containing 100 mg/L Eu(NO 3 ) 3 spiked with 152,154 Eu tracer.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Obtained kinetics data were fitted into three different kinetics models: Lagergren first order ( SE1 ), pseudo-second order ( SE2 ), and intraparticle diffusion ( SE3 ) (Figures S1–S3). Regression coefficient analysis showed that sorption kinetics fits best in the pseudo-second order model. The sorption isotherm shown in Figure C describes the maximum sorption capacity for UO 2 2+ ≈ 193 mg g –1 and Th 4+ ≈ 227 mg g –1 .…”
Section: Resultsmentioning
confidence: 99%